Black Celebrity, Racial Politics, and the Press Framing Dissent - Jackson, Sarah J. (Routledge Transformations in Race and Media, 2014)
Shifting understandings and ongoing conversations about race, celebrity, and protest in the twenty-first century call for a closer examination of the evolution of dissent by black celebrities and their reception in the public sphere. This book focuses on the way the mainstream and black press have covered cases of controversial political dissent by African American celebrities from Paul Robeson to Kanye West. Jackson considers the following questions: 1) What unique agency is available to celebrities with racialized identities to present critiques of American culture? 2) How have journalists in both the mainstream and black press limited or facilitated this agency through framing? What does this say about the varying role of journalism in American racial politics? 3) How have framing trends regarding these figures shifted from the mid-twentieth century to the twenty-first century? Through a series of case studies that also includes Eartha Kitt, Sister Souljah, and Mahmoud Abdul-Rauf, Jackson illustrates the shifting public narratives and historical moments that both limit and enable African American celebrities in the wake of making public politicized statements that critique the accepted racial, economic, and military systems in the United States.